Culture as a Pathway to Maximizing the Stress-Buffering Role of Social Support. Issue 3 (August 2018) - Campos, Belinda; Yim, Ilona S.; Busse, David
We theorized that sociocultural contexts characterized by a form of interdependence that emphasizes mutual obligations, emotional positivity, and readily accessible social support from family may maximize the benefits of social support. This form of interdependence characterizes Latino culture and is captured by the cultural value familism . Eighty-six Latino and non-Latino participants completed measures of familism and perceived social support before taking part in a standardized laboratory stress task that elicits cortisol reactivity. Cortisol reactivity is an indicator of bodily response to stress that is linked to vulnerability to the adverse effects that stress can have on future health. As predicted, results revealed a moderated mediation pattern. Conditional process analysis showed that familism was indirectly linked to cortisol reactivity through perceived social support, and this mediation effect was moderated by sociocultural context; stress buffering effects were only observed in the Latino sample. These novel findings highlight the role of culture and, specifically, familism in Latinos, for maximizing the benefits that social support can have for stress physiology implicated in long-term health outcomes.